Claw enforcement - Ryan, Sofie, 1958- (Ryan, Sofie, 1958- Second Chance cat mystery., 2020)
Sarah Grayson owns a delightful secondhand shop in the small town of North Harbor, Maine, where she and her rescue cat, Elvis, are always finding themselves up to their whiskers in trouble. With the help of a quirky group of senior citizens<U+2014>who call themselves Charlotte<U+2019>s Angels and work out of the store<U+2014>they solve crimes both new and vintage. Local squabbles about property development have the town in quite a state of drama<U+2014>and it seems like someone may even be upset enough to kill. When a local man involved in the real estate quagmire falls over dead at a reception to celebrate the harbor front<U+2019>s redevelopment, Sarah gets roped in to investigate by her own IT expert, Mr. P., who has long known the victim<U+2019>s stepfather. Between Sarah, Elvis and Charlotte<U+2019>s Angels, the killer is sure to have claws for concern.